Іnnovation technologies in the gut organs surgery - V. М. Меlnyk; Ye. М. Shepetko; І. І. Polovnikov; О. І. Poyda (Клінічна хірургія, 2018)
Objective. To improve the surgical treatment results in patients, suffering the gut organs diseases, due to its sophistication and elaboration of modern innovation technologies.